Rice Paddy Farming Performance, Rice Prices, and Food Inflation in Jambi Province - bin Abdullah, Zainuddin (Jurnal Dinamika Sosial Ekonomi, 2024)
Jambi Province's ability to produce rice has declined in the last 5 years (2018 to 2022). Changes in the ratio of rice prices to other commodities are likely to be the cause of land use for rice crops decreasing, especially tidal and rainfed land areas. The stagnation of irrigated rice fields, the quality of rice seeds, the allocation of subsidized fertilizers below the needs, is likely to be a factor in the low productivity of paddy rice yields in the 2018 to 2022 period. Jambi Province experienced an average deficit of 5596 tons per month in the 2018 to 2020 period, and 9537 tons per month in the 2021 to 2022 period. Rice prices at the rural consumer level in Jambi Province are relatively more stable with a slow increase. This is likely related to the less volatile interprovincial rice price transmission driven by the smooth distribution of rice and the impact of the government's market stabilization program. City food inflation in 2018 and 2019 was more stable within a low range. However, it became more volatile from 2020 to 2022. The increase in city food inflation generally occurs from the middle to the end of the year. Rice has the highest weight in the food price index used in calculating food inflation. The growing rice deficit in Jambi Province creates vulnerability in controlling food inflation, especially in urban areas. Higher food inflation is feared to threaten household purchasing power and food security